IMPLEMENTASI MAQASID AL-SYARI’AH DALAM MEMPERSATUKAN UMAT - Mukhlis Mukhtar (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2020)
This article discusses the implementation of Maqasid Al-Shari'ah in uniting the Ummah. From the results of the discussion affirms that Maqasid al sharia is the values ​​and targets of syara 'which are implied in all or the largest part of its laws. These values ​​and targets are seen as sharia goals and secrets, established by al-shari 'in every legal provision. The implementation of the principles of Maqasid al sharia is contained in every principle of Pancasila as the State Foundation. Maqasid al-shari'ah is not designed for the interests of certain communions or religious groups, as confirmed by Allah (shari'ah maker) and Muhammad peace be upon him. (Shari'ah bearer) is the spreader of mercy for the universe (rahmatan lil alamin), not just for Muslims.